2010
DOI: 10.1039/c0cc01041c
|View full text |Cite
|
Sign up to set email alerts
|

HSA coated MnO nanoparticles with prominent MRI contrast for tumor imaging

Abstract: We report in this Communication a facile, two-step surface modification strategy to achieve manganese oxide nanoparticles with prominent MRI T1 contrast. In a U87MG glioblastoma xenograft model, we confirmed that the particles can accumulate efficiently in tumor area to induce effective T1 signal alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 20 publications
0
108
2
2
Order By: Relevance
“…2a) is obtained by measuring the relaxation rate of water protons with increasing concentrations of NPs, and is calculated to be 8.26 mM −1 s −1 . This value is twice higher than that of Gd-DTPA (4.11 mM −1 s −1 ) and the highest value reported to date for Mn-based NPs (Table 1)2324424344454647. These nanocrystals are also tested in PBS solution in order to simulate the culture medium.…”
Section: Resultsmentioning
confidence: 87%
“…2a) is obtained by measuring the relaxation rate of water protons with increasing concentrations of NPs, and is calculated to be 8.26 mM −1 s −1 . This value is twice higher than that of Gd-DTPA (4.11 mM −1 s −1 ) and the highest value reported to date for Mn-based NPs (Table 1)2324424344454647. These nanocrystals are also tested in PBS solution in order to simulate the culture medium.…”
Section: Resultsmentioning
confidence: 87%
“…The massive uptake by the liver was evidenced in the PET data, as soon as one hour aer injection. 55 These results indicated that MnO particles, as many other inorganic core nanoparticles in that size range, are strongly sequestrated by the RES if they are not adequately coated with molecules preventing or delaying their opsonisation. RES-sequestrated nanoparticles are more susceptible to remain in the organism for longer periods, which, in the case of Mn 2+ -containing nanoparticles, would represent a toxicological risk.…”
Section: Manganese Biodistribution Studymentioning
confidence: 95%
“…6,7 Therefore, attention has shifted to alternative agents such as manganese (Mn)-based complexes [8][9][10][11] and nanoparticles (NPs), [12][13][14][15] which has produced encouraging results for both in vitro and in vivo MR imaging of cancer. [16][17][18] For instance, MnO NPs have been successfully used for T 1 -weighted MR imaging of metastatic brain tumors. 19 However, compared with gadolinium-based contrast agent, [20][21][22][23] most of the Mn-based NPs exhibit relatively low r 1 relaxivity, 24 which may limit their uses in sensitive T 1 -weighted MR imaging of tiny gliomas.…”
Section: Introductionmentioning
confidence: 99%